Etude des paramètres biochimiques et physiologiques de l’effet exogène de l’extrait de Punica granatum sur les plantules de Vicia faba sous stress métallique (Pb ) - Djellabi Rahma; Chafai Asma (My University, 2022)
Lead is one of the most toxic heavy metals and causes considerable damage to plants.This study aimed to estimate and compare the level of lead contamination and the antioxidantpower of Punica granatum extract in broad bean (Vicia faba) plant. This plant is used as amodelin ecotoxicologicalstudiesbecauseofitslargebiomassandshortvegetativecycle. The objective of our work is to study the influence of lead in the form of nitratesPb(NO3)2 in quantity 100µmol/l, in the presence or not of the extract of Punica granatum inquantityof1g/lonthemorpho-physiologicalbehavior,thebiochemicalandcytogeneticmarkers.Thistreatmentwasapplied twiceduring thevegetative cycle ofthe plant The results found reveal that the development of the plants in front of the stress isstrongly inhibited and the morphogenesis of the two parts of this plant turns out to be verymodified following this stress. The presence of lead decreases the production of biomassparametersaccompaniedbyareductionofthewater contentintherootparts.Theseresultsalsoshowadecreasein solublesugarsandproline,whilethepresenceofleadindicatesanaccumulation of photosynthetic pigments, protein content and electrolyte leakage and MSI,expressing a mechanism of regulation of the internal potential in front of the action of metallicstress. TheapplicationofPunicagranatumextractcausesanaccumulationofcatalase (CAT),ascorbateperoxidase(APX)andhydrogenperoxideactivitycomparedtountreatedplants. These results suggest that the presence of lead modifies the normal functioning anddevelopment of the plants by disturbances on the morpho-physiological, biochemical andcytogenetic plant, and that the application of the extract of Punica granatum helps to reducethe harmful effect of the stress (lead) on the bean plants by developing the tolerance bystimulationandtheprotectionoftheplantsagainstthestress ------------------------------------------------------------------------------------------------------------------------------------------------------------------- الرصاصهوأحدأكثرالمعادنالثقيلةسمية،يتسببفيأضرارجسيمةللنباتات.غرضنامنهذهالدراسةهوتقييمومقارنةمستوىالتلوثبالرصاصوبالمقابلدراسةالقوةالمضادةللأكسدةلمستخلصقشورالرمانعلىمستوىنباتاتالفول. الهدفمنعملناهودراسةتأثيرالرصاصبكمية١٠٠ميكرومول / لتر،فيوجودأوعدموجودمستخلصقشورالرمانبمقدار١جرام / لتر،علىالسلوكالمورفولوجيوالفيزيولوجيوالعلاماتالكيميائيةالحيويةوالوراثةالخلويةحيثتم تطبيقهداالعلاجمرتينخلالالدورةالخضريةللنبات. النتائجالمتحصلعليهاتوضحأنالاجهاديؤثرعلىنموالنباتاتبشكلسلبي،حيثيؤديوجودالرصاصإلىتقليلإنتاجالمقاييسالحيويةمعتقليلمحتوىالمياهفيالأجزاءالجذرية.تظهرالنتائجأيضًاانخفاضًافيالسكرياتالقابلةللذوبانوالبرولين،أيضايشيرإلىتراكمالأصباغالضوئيةومحتوىالبروتينوتسربالإلكتروليت،ممايعبرعنآليةلتنظيم الإمكاناتالداخليةفيمواجهةالاجهادالمعدني.فيحينيشكلتطبيقمستخلصقشورالرمانزيادةنشاطالكاتالازوبيروكسيدازالأسكوربيتوبيروكسيدالهيدروجينمقارنةبالنباتاتغيرالمعالجة. أثبتتالنتائجفيالأخيرأنوجودالرصاصيغيرالأداءالطبيعيللنباتاتوتطورهامنخلالالاضطراباتعلىالمستوىالمورفولوجيالفيزيولوجيوالكيميائيالحيويوالخلويالوراثي،وأنتطبيقمستخلصقشورالرمانيساعدعلىتقليلالتأثيرالضارللإجهاد)الرصاص(علىنباتاتالفولحيثيطورالتحملعنطريقتحفيزالنظامالمضادللأكسدةوحمايتهامنالإجهاد ---------------------------------------------------------------------------------------------------------------------------------------------------------------- Leplombestl'undesmétauxlourdslesplustoxiques,ilcausedesdégâtsconsidérablesau niveau des plantes. Cette étude vise à estimer et à comparer le niveau de contamination parleplombainsiquelepouvoirantioxydantdel’extraitdePunicagranatumauniveaudelaplantedelafève(Viciafaba). L’objectif de notre travail est d’étudier l’influence du plomb sous forme de nitratesPb(NO3)2 en quantité 100µmol/l, en présence ou pas de l’extrait de Punica granatum enquantité de 1g/l sur le comportement morpho-physiologique, les marqueurs biochimiques etcytogénétiques,Ce traitementaétéappliquédeuxfoisdurantlecyclevégétatifdelaplante. Les résultats trouvés révèlent que le développement des plantes face au stress se trouvefortementinhibéetlamorphogénèsedesdeuxpartiesdecetteplantes’avèretrèsmodifiéessuiteà ce stress.La présence duplomb diminuelaproduction des paramètres des biomassesaccompagnéed’uneréductiondelateneureneauauniveaudespartiesracinaires.Cesrésultatsmontrentégalementunediminutiondessucressolublesetdelaproline,Tandisquelaprésenceduplombindiqueuneaccumulationdespigmentsphotosynthétiques,lateneurenprotéineetlafuite d’électrolyte et MSI, exprimant un mécanisme de régulation du potentiel interne face àl’actiondustressmétallique. L’application de l’extrait de Punica granatum provoque une accumulation de l’activitédelacatalase(CAT),del’ascorbateperoxydase(APX)etdeperoxyded’hydrogèneparrapportauxplantes nontraitées. Ces résultats suggèrent que la présence du plomb modifie le fonctionnement et ledéveloppement normal des plantes par des perturbations sur le plan morpho-physiologique,biochimiques et cytogénétiques, et que l’application de l’extrait de Punica granatum aide àréduire l’effet néfaste du stress (plomb) sur les plantes de fève en développent la tolérance parstimulationetla protectiondesplantescontreaustress.